2022
DOI: 10.1002/ajp.23413
|View full text |Cite
|
Sign up to set email alerts
|

Diet, activity patterns, and home range use in forest and cultivated areas for one wild group of endangered crested capuchin monkeys (Sapajus robustus) in Reserva Natural Vale, Espírito Santo, Brazil

Abstract: Robust capuchin monkeys (Sapajus spp.) are distributed widely in the Neotropics and may be able to survive in modified landscapes because of their omnivorous, opportunistic diet. The poorly known and endangered crested capuchin monkey (Sapajus robustus) is endemic to the Atlantic Forest in Bahia, Minas Gerais and Espírito Santo states, Brazil. We collected data on diet and home range for a crested capuchin group with access to forest and cultivated areas. We hypothesized that with access to cultivated exotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(45 citation statements)
references
References 37 publications
0
45
0
Order By: Relevance
“…We predict that at least some wild crested capuchins use tools. Due to their Atlantic Forest habitat, crested capuchins are surrounded with raw materials and likely experience marked seasonal variation in fruit availability (Martins et al, 2022; Spagnoletti et al, 2012), both of which contribute to the opportunity to create tools for solving foraging challenges. Furthermore, as a gregarious primate, the ample raw materials allow for the opportunity of tool‐mediated social interaction such as throwing and waving.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We predict that at least some wild crested capuchins use tools. Due to their Atlantic Forest habitat, crested capuchins are surrounded with raw materials and likely experience marked seasonal variation in fruit availability (Martins et al, 2022; Spagnoletti et al, 2012), both of which contribute to the opportunity to create tools for solving foraging challenges. Furthermore, as a gregarious primate, the ample raw materials allow for the opportunity of tool‐mediated social interaction such as throwing and waving.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon of intergroup variation in tool use can be seen in S. xanthosternos (Canale et al, 2009), the species most closely related to S. robustus (Lima et al, 2018; Lynch Alfaro et al, 2012). The single‐year‐long research study to date of wild crested capuchins (Martins, 2010; Martins et al, 2022) may have simply observed by chance a group that did not use tools, and the species remains severely understudied. Even in populations where tool use does not occur, individuals in this species may be using their manual and cognitive skills to deal with other complex challenges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the exploitation of exotic species could be an adaptation to altered environments, and a response to anthropogenic changes. Martins et al (2022) studying Sapajus robustus recorded the use of six cultivated exotic species, which may have favored the maintenance of a smaller home range when compared to other conspecifics and congenerics. This consumption of exotic cultivated food sources can lead to conflicts between humans and wildlife, as losses in harvest could be attributed to primates or other species.…”
mentioning
confidence: 99%